Estrategias metodológicas para mejorar el proceso de enseñanza aprendizaje del bloque curricular de relaciones y funciones del noveno año de educación general básica de la unidad educativa intercultural bilingüe Mushuk Rimak de la parroquia San Lucas, cantón y provincia de Loja, periodo 2012 – 2013 - Sarango Condolo, Segundo Abel (2016)
This research is a study on the methodological strategies to improve teaching and learning block Curricular Relations and Functions of the Ninth Year of General Education Basic Education Unit Intercultural Bilingual Mushuk Rimak, Parish San Lucas, canton and province Process Loja, period 2012 - 2013. the overall objective of this research is to determine how the methodological strategies used by teachers influence the teaching learning block relationships and functions in the Ninth Year Basic General Education Intercultural Bilingual Education Unit process "Mushuk Rimak" parish San Lucas, canton and province of Loja, 2012-2013. The methodology that was considered for this research was the use of descriptive method to classify information, analytic-synthetic method for the management of research problem and argue and argue the facts; the deductive method to organize the observed facts and generalize the most important characteristics; hypothetical deductive method was used for the approach of hypothesis and verification and to determine the conclusions and recommendations. Finally, the technique used was the survey of students and teachers through the design of a previous questionnaire. From the results it is observed that teachers are using some chords for skill development block relationships and functions methodological strategies, so that limits the student to develop the skills set for the tenth year of basic education in the area mathematics and said block; recommending intensive training teachers to achieve these standards to enable it to properly fulfill its function body.